1975
DOI: 10.1111/j.1751-0813.1975.tb09404.x
|View full text |Cite
|
Sign up to set email alerts
|

The Serological Diagnosis of Bovine Brucellosis: An Evaluation of the Complement Fixation, Serum Agglutination and Rose Bengal Tests

Abstract: In a collaborative investigation in which 4 laboratories took part, the Rose Bengal Test (RBT), Serum Agglutination Test (SAT) and 4 different Complement Fixation (CFT) techniques were evaluated in selected cattle for the diagnosis of bovine brucellosis, by comparing the results they gave with the bacteriological examination of a selection of lymph nodes taken from the same animals at slaughter. The RBT correctly classified all but 1 of 79 culture-positive cattle, but was more often positive in culture-negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
5

Year Published

1976
1976
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 2 publications
0
31
0
5
Order By: Relevance
“…The test was conducted as per the procedure recommended by Alton et al (1975) and Nilsen and Dunkan (1990). The antigen was obtained from Institute Pourquier, Montpellier, France.…”
Section: Rose Bengal Plate Test (Rbpt)mentioning
confidence: 99%
See 1 more Smart Citation
“…The test was conducted as per the procedure recommended by Alton et al (1975) and Nilsen and Dunkan (1990). The antigen was obtained from Institute Pourquier, Montpellier, France.…”
Section: Rose Bengal Plate Test (Rbpt)mentioning
confidence: 99%
“…Sera with strong reaction, more than 75% fixation of complement (3+) at a dilution of 1: 5 and at least 50% fixation of complement (2%) at a dilution of 1:10 and at dilution of 1:20 were classified as positive (Alton , et al, 1975;OIE, 2004).…”
Section: Complement Fixation Test (Cft)mentioning
confidence: 99%
“…Taken into consideration the patient's travel history to Inner Mongolia, which is one of the major pastoral areas of China (15), prior to a fever, a number of laboratory tests were completed to determine a positive diagnosis of brucellosis. Rose-Bengal Plate Test (RBPT) was positive (16) and as a result, a standard serum agglutination test (SAT) was performed as previously described (17), using the SAT antigen (cat. no.…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…This result could be predicted from the low sensitivity of the SAT to IgG antibody (Chappel et al 1978). Alton, Maw, Rogerson & McPherson (1975b) found that 11 % of animals from which B. abortus could be isolated gave SAT reactions of less than 100 i.u./ml. The present study has shown that an even greater problem may exist.…”
Section: Serum Aggluttnation Testmentioning
confidence: 99%